Analysis Of The Design And Construction Of A Water Spinach (Ipomoea Aquatica) Vegetable Drying Chamber With A Spiral Type Heater - Wahid, Okon Agustyan; Nugroho, Wahyu; Kholili, Navik; Khusna, Dwi; Nugroho, Alfi; Muchid, Mochammad (Journal of System Engineering and Technological Innovation, 2024)
The food drying process is an innovative method to change the process of reducing the water content of fresh food products of plant origin to slow down the emergence and growth of unwanted microorganisms. This heating system has four heating elements, where the heating elements used have a power of 1200W because each heating element has a power of 300W. During the drying process, it is known that the average air temperature in the drying room is higher when using solar energy compared to a heating system. The average temperature measurement during the day is 38°C. The measurement results tend to be constant, with an average of 34°C for 7 hours using the heating system. The battery voltage shows an increase every hour. At 08:30 am the battery voltage was 12.3V, and until 16.00 the voltage was 13.57V. This dryer is sourced from solar energy because using solar for drying requires a longer time, namely 8 hours (08.30-16.00), compared to using a heating system for 7 hours.